Titanium-based surface perforated pipe and preparation method thereof
By coating the surface of titanium tubes with titanium powder, titanium-nickel alloy powder, and nickel-titanium fibers to form a porous layer, the problem of poor heat transfer performance of titanium-based heat exchange tubes is solved, achieving efficient boiling heat transfer performance and enhanced bonding strength.
Patent Information
- Application Number
- CN202411437722.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-10
AI Technical Summary
Existing titanium-based heat exchange tubes have not achieved good results in improving heat transfer performance, and traditional preparation methods are difficult to achieve the preparation of efficient porous structures.
Using titanium powder, titanium-nickel alloy powder and nickel-titanium fiber as the main raw materials, the solution is coated onto the surface of the titanium tube, dried under the action of a magnetic field and heat-treated to form a porous layer with high bonding strength, uniform pores and excellent heat transfer performance.
The prepared titanium-based porous tubes achieved high bonding strength and excellent boiling heat transfer performance under low-temperature sintering conditions, with the heat transfer coefficient increased by 2.3 to 4.5 times and the porosity and pore size distribution being uniform.
Smart Images

Figure CN119287364A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of heat exchange tube preparation, and in particular to a titanium-based surface porous tube and a preparation method thereof. Background Art
[0002] The surface porous tube is a high-efficiency heat exchange element that enhances the heat transfer efficiency by manufacturing a porous structure on the surface of the heat exchange tube. It is widely used in evaporators, reboilers, condensers, vaporizers, etc. in the fields of petroleum, chemical industry, metallurgy, seawater desalination, electronic chip heat dissipation, nuclear industry, etc.
[0003] Depending on the application conditions, the materials of heat exchange tubes mainly include carbon steel, stainless steel, copper-nickel alloy and titanium. Among them, carbon steel has poor corrosion resistance. Although stainless steel and copper-nickel alloy have good corrosion resistance, in some special corrosive environments, the surface passivation film is destroyed, resulting in severe local corrosion of the tube. In comparison, titanium has excellent corrosion resistance and high specific strength and specific stiffness, and is widely used in heat exchanger equipment with corrosion resistance requirements.
[0004] Due to the poor processing performance of titanium, it is difficult to prepare titanium-based surface porous tubes using traditional machining methods such as threads, grooves, and fins. The sintering method is a relatively easy method to enhance heat transfer. By sintering a metal porous layer with a specific pore size, porosity, and thickness on the surface of the base tube, boiling heat transfer is enhanced, and the heat transfer efficiency of the heat exchange tube can be increased by 2 to 10 times. However, there are currently few reports on the preparation of titanium-based surface porous tubes using the sintering method.
[0005] Chinese patent CN113834365A discloses a method for preparing a high-flux high-titanium heat exchange tube. By mixing 0-5.0wt% of connecting metal into titanium powder, the connection stability between the titanium porous layer and the base tube after sintering is improved. However, the sintering temperature used is relatively high, reaching 1200°C, which is easy to damage the performance of the base tube, and the porous layer is relatively thick, and the effect of enhancing boiling heat transfer is limited. The document "A method and experimental test for enhancing heat transfer in a titanium tube heat exchanger" (Cheng Ning. A method and experimental test for enhancing heat transfer in a titanium tube heat exchanger [J]. Energy Conservation, 2021.) uses spring wire inserts to enhance heat transfer in the tube, and the heat transfer coefficient of the enhanced tube is measured to be 68% to 93% higher than that of the light tube. Chinese patent CN 116180190A discloses a technical solution for preparing a titanium-based high-flux heat exchange tube by combining a self-weight coating method with an electrochemical method, which can increase the heat transfer efficiency of the heat exchange tube by 20% to 40%.
[0006] In summary, although the existing titanium-based heat exchange tube preparation method has improved the heat transfer performance of the titanium-based heat exchange tube to a certain extent, the improvement effect is not good. Summary of the invention
[0007] In view of the above-mentioned shortcomings of the prior art, an object of the present invention is to provide a titanium-based surface porous tube and a preparation method thereof, so as to solve the problem of poor heat transfer performance of titanium-based heat exchange tubes in the prior art.
[0008] To achieve the above objectives and other related objectives, the present invention is achieved through the following technical solutions.
[0009] The first aspect of the present invention is to provide a method for preparing a titanium-based surface porous tube, comprising the following steps:
[0010] (1) pretreating a substrate to obtain a pretreated substrate;
[0011] (2) mixing the binder and the solvent, aging, and obtaining a colloidal solution;
[0012] (3) adding titanium powder, titanium-nickel alloy powder and nickel-titanium fiber wire to the colloidal solution obtained in step (2) in sequence, stirring to obtain a powder slurry;
[0013] (4) coating the powder slurry obtained in step (3) on the surface of the pretreated substrate obtained in step (1), and drying under magnetic field conditions to obtain a surface film tube;
[0014] (5) heat-treating the surface film tube obtained in step (4), cooling it, and obtaining a surface porous tube.
[0015] The second aspect of the present invention is to provide a titanium-based surface porous tube, which is prepared by the preparation method described above.
[0016] In some embodiments of the present invention, the titanium-based surface porous tube comprises a substrate and a porous layer formed on the surface of the substrate; preferably, the thickness of the porous layer is 200 to 400 μm.
[0017] As described above, the titanium-based surface porous tube and the preparation method thereof of the present invention have the following beneficial effects:
[0018] (1) The surface porous layer of the titanium-based surface porous tube prepared by the present invention is mainly made of titanium powder, titanium-nickel alloy powder and nickel-titanium fiber wire, which is coated on the surface of the titanium tube substrate through a colloidal solution. The melting point of the titanium-nickel alloy powder is relatively low, and a liquid phase is generated during the sintering process, which promotes the titanium powder to form a strong metallurgical bond at a relatively low sintering temperature, thereby effectively reducing the sintering temperature. On the other hand, the nickel-titanium fiber wire is radially distributed along the radial direction of the titanium tube under the action of the magnetic field, which improves the permeability of the porous layer pores and the uniform distribution of the pore size. The titanium-based surface porous tube thus prepared has a low sintering temperature, a good bonding strength between the interface porous layer and the substrate, and better boiling heat transfer performance;
[0019] (2) The surface porous layer prepared by the present invention is mainly composed of α-Ti, TiNi, Ti2Ni and TiNi3 phases. TiNi, Ti2Ni and TiNi3 phases are all intermetallic compounds, which play a role of dispersion strengthening in the porous layer and effectively improve the mechanical properties of the titanium-based surface porous tube. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Shown is the Ti-Ni phase diagram of the surface porous layer of the titanium-based surface porous tube of the present invention. DETAILED DESCRIPTION
[0021] In order to make the purpose of the invention, technical solutions and beneficial technical effects of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. People familiar with this technology can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.
[0022] The surface porous layer of the titanium-based surface porous tube prepared by the present invention uses titanium powder, titanium-nickel alloy powder and nickel-titanium fiber wire as main raw materials. On the one hand, the melting point of the titanium-nickel alloy powder is relatively low, and a liquid phase is generated during the sintering process, which prompts the titanium powder to form a strong metallurgical bond at a relatively low sintering temperature, thereby effectively reducing the sintering temperature. On the other hand, the nickel-titanium fiber wire is radially distributed along the radial direction of the titanium tube under the action of a magnetic field, which improves the permeability of the porous layer pores and the uniform distribution of the pore size, thereby ensuring the excellent boiling heat transfer performance of the surface porous tube.
[0023] The surface porous layer prepared by the present invention is mainly composed of α-Ti, TiNi, Ti2Ni and TiNi3 phases, and TiNi, Ti2Ni and TiNi3 phases are all intermetallic compounds, which play a role of dispersion strengthening in the porous layer and effectively improve the mechanical properties of the titanium-based surface porous tube.
[0024] The first aspect of the present invention is to provide a method for preparing a titanium-based surface porous tube, comprising the following steps:
[0025] (1) pretreating a substrate to obtain a pretreated substrate;
[0026] (2) mixing the binder and the solvent, aging, and obtaining a colloidal solution;
[0027] (3) adding titanium powder, titanium-nickel alloy powder and nickel-titanium fiber wire to the colloidal solution obtained in step (2) in sequence, stirring to obtain a powder slurry;
[0028] (4) coating the powder slurry obtained in step (3) on the surface of the pretreated substrate obtained in step (1), and drying under magnetic field conditions to obtain a surface film tube;
[0029] (5) heat-treating the surface film tube obtained in step (4), cooling it, and obtaining a surface porous tube.
[0030] In some embodiments of the present invention, the base pipe has an outer diameter of 19-32 mm and a wall thickness of 2-3 mm.
[0031] In some embodiments of the present invention, the pretreatment in step (1) is surface treatment of the substrate, followed by cleaning and drying. Preferably, the surface treatment is selected from one or more of pickling, laser rust removal, mechanical grinding, sandblasting, and passivation; further preferably, the surface treatment is selected from sandblasting, and the sandblasting treatment is not particularly limited, and a conventional sandblasting process can be used; specifically, the sandblasting material selected for sandblasting is aluminum oxide sand or zirconium oxide sand, the particle size of the sandblasting material is 20-100 mesh, and the sandblasting pressure is 0.1-1MPa; the cleaning is carried out using water or alcohol; the drying temperature is 60-80°C; the drying time is 0.5-2h;
[0032] In some embodiments of the present invention, the substrate in step (1) is selected from titanium or titanium-based alloys. Preferably, the substrate is a titanium tube.
[0033] In some embodiments of the present invention, the binder in step (2) is selected from one or more of polyvinyl alcohol, polyethylene glycol, polyvinyl butyral, polyvinyl pyrrolidone, and methyl cellulose; the present application has no special limitation on the sources of polyvinyl alcohol, polyethylene glycol, polyvinyl butyral, polyvinyl pyrrolidone, and methyl cellulose, and commercially available products of polyvinyl alcohol, polyethylene glycol, polyvinyl butyral, polyvinyl pyrrolidone, and methyl cellulose frequently used by those skilled in the art may be used.
[0034] In some embodiments of the present invention, the solvent in step (2) is selected from one or more of water, methanol, ethanol, ethylene glycol, benzene, and toluene. Preferably, the solvent in step (2) is selected from water or ethanol;
[0035] In some embodiments of the present invention, the mass ratio of the binder to the solvent in step (2) is 1:10-40; specifically, it can be 1:10-15, 1:15-25, 1:25-35, 1:35-40; typical but non-limiting, for example, is 1:10, 1:15, 1:25, 1:30, 1:40.
[0036] In some embodiments of the present invention, the aging time in step (2) is 12 to 24 hours; specifically, it can be 12 to 15 hours, 15 to 20 hours, or 20 to 24 hours; typically but not limitingly, for example, it is 12 hours, 15 hours, 20 hours, or 24 hours.
[0037] In some embodiments of the present invention, the mixing temperature in step (2) is 40-90°C; specifically, the mixing temperature can be 40-60°C, 60-80°C, 80-90°C; typical but non-limiting examples are 40°C, 60°C, 80°C, and 90°C.
[0038] In some embodiments of the present invention, the mass ratio of titanium powder, titanium-nickel alloy powder and nickel-titanium fiber filament in step (3) is 3-5:1:0.2-0.5; specifically, the mass ratio can be 3-4:1:0.2-0.4, 4-5:1:0.4-0.5; typical but non-limiting examples are 3:1:0.2, 4:1:0.3, and 5:1:0.2.
[0039] In some embodiments of the present invention, the average particle size of the titanium powder in step (3) is 50-150 μm; specifically, the average particle size may be 50-70 μm, 70-100 μm, 100-130 μm, 130-150 μm; typical but non-limiting examples include 50 μm, 70 μm, 100 μm, 130 μm, and 150 μm.
[0040] In some embodiments of the present invention, the average particle size of the titanium-nickel alloy powder in step (3) is 20-50 μm; specifically, the average particle size can be 20-30 μm, 30-40 μm, 40-50 μm; typically but not limiting, for example, 20 μm, 30 μm, 40 μm, 50 μm. The nickel content of the titanium-nickel alloy powder is 28 wt.% to 38 wt.%.
[0041] In some embodiments of the present invention, the wire diameter of the nickel-titanium fiber wire in step (3) is 10-30 μm, and the length is 100-300 μm; specifically, the wire diameter of the nickel-titanium fiber wire can be 10-20 μm, 20-30 μm; typically but not limiting, for example, 10 μm, 20 μm, 30 μm; the length of the nickel-titanium fiber wire can be 100-150 μm, 150-200 μm, 200-250 μm, 250-300 μm, typically but not limiting, for example, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm. The titanium content of the nickel-titanium fiber wire is 22 wt.% to 45 wt.%.
[0042] In some embodiments of the present invention, the mass ratio of the titanium powder, the titanium-nickel alloy powder and the nickel-titanium fiber wire to the colloidal solution in step (3) is 1.5 to 3.5:1. Specifically, it can be 1.5 to 2:1, 2 to 3.5:1; typically but not limitingly, for example, 1.5:1, 2:1, 3.5:1.
[0043] In some embodiments of the present invention, the thickness of the surface film layer of the surface film tube in step (4) is 200-400 μm; specifically, the thickness of the surface film layer can be 200-300 μm, 300-400 μm; typically but not limiting, for example, 200 μm, 300 μm, 400 μm.
[0044] In some embodiments of the present invention, the magnetic induction intensity of the magnetic field drying in step (4) is 0.3-0.7T; specifically, the magnetic induction intensity can be 0.3-0.5T, 0.5-0.7T; typically but not limiting, for example, 0.3T, 0.5T, 0.7T.
[0045] In some embodiments of the present invention, the drying temperature is 50-70°C; specifically, the temperature can be 50-60°C, 60-70°C; typically but not limitatively, for example, 50°C, 60°C, 70°C; the drying time is 1-2h; specifically, the time can be 1-1.5h, 1.5-2h; typically but not limitatively, for example, 1h, 1.5h, 2h.
[0046] In some embodiments of the present invention, the heat treatment in step (5) includes degreasing and sintering; the degreasing temperature is 250-450°C, specifically, the degreasing temperature can be 250-300°C, 300-350°C, 350-400°C, 400-450°C; typically but not limiting, for example, 250°C, 300°C, 350°C, 400°C, 450°C; the holding time is 30-90min; specifically, the holding time can be 30-50min, 50-80min, 80-90min; typically but not limiting, for example, 30min, 50min, 80min, 90min; the degreasing temperature is The rate is 2-5°C / min; the sintering temperature is 900-1100°C, specifically, the sintering temperature can be 900-940°C, 940-980°C, 980-1000°C, 1000-1050°C, 1050-1100°C; typically but not limiting, for example, 900°C, 940°C, 980°C, 1000°C, 1050°C, 1100°C; the heat preservation time is 20-60min; specifically, the heat preservation time can be 20-30min, 30-45min, 45-60min; typically but not limiting, for example, 20min, 30min, 45min, 60min. The heating rate of the sintering is 5-10°C / min.
[0047] In some embodiments of the present invention, the heat treatment in step (5) is performed under vacuum or inert gas atmosphere; wherein the inert gas is selected from helium or argon; preferably, the heat treatment is performed under vacuum conditions.
[0048] In some embodiments of the present invention, the cooling in step (5) includes furnace cooling and / or water cooling.
[0049] The second aspect of the present invention is to provide a titanium-based surface porous tube, which is prepared by the preparation method described above.
[0050] In some embodiments of the present invention, the titanium-based surface porous tube includes a substrate and a porous layer formed on the surface of the substrate; the thickness of the porous layer is 200-400 μm; specifically, the thickness of the porous layer can be 200-300 μm, 300-350 μm, 350-400 μm; typical but non-limiting, for example, 200 μm, 300 μm, 350 μm, 400 μm; the substrate is selected from titanium or titanium-based alloy.
[0051] The present invention is further described below by way of examples, but the scope of the present invention is not limited thereto.
[0052] When the embodiment gives a numerical range, it should be understood that, unless otherwise specified in the present invention, the two endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art. If specific conditions are not specified in the embodiment, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for all reagents or instruments, they are conventional products that can be purchased commercially. In addition to the specific methods, equipment, and materials used in the embodiments, according to the grasp of the prior art by those skilled in the art and the record of the present invention, any method, equipment, and material of the prior art similar or equivalent to the method, equipment, and material in the embodiments of the present invention can also be used to realize the present invention.
[0053] The test instruments and test conditions used in the examples are as follows:
[0054] Test of bonding performance between porous layer and substrate:
[0055] The bonding performance between the porous layer and the substrate is tested by the shear strength method, that is, the shear strength of the porous layer is used to evaluate the bonding strength between the porous layer and the substrate. The shear strength refers to the limit capacity of the contact surface between the porous layer and the substrate to withstand the axial shear force per unit area, and its calculation formula is as follows:
[0056]
[0057] In the formula, τ b is the shear strength of the porous layer, F is the maximum load when the porous layer is peeled off, D is the outer diameter of the substrate, and W is the axial length of the porous layer.
[0058] Heat transfer performance test:
[0059] The heat transfer performance of the surface porous tube is measured by a pool boiling test device. The heat transfer coefficient is used to evaluate the heat transfer performance of the heat exchange tube. The larger the heat transfer coefficient, the better the heat transfer performance of the heat exchange tube. Specifically, with propane as the boiling medium outside the tube, the heat flow Q at each voltage value can be obtained by multiplying the condensate volume m and the latent heat of vaporization γ and dividing by the time t, that is, Q = (m·γ) / t; heat flux q = Q / A; boiling heat transfer coefficient h = q / (t w -t sat ), where A is the effective heat transfer area, t w is the outer wall temperature of the tube, t sat is the medium temperature.
[0060] Example
[0061] Example 1
[0062] The method for preparing the titanium-based surface porous tube of this embodiment comprises the following steps:
[0063] (1) The surface of the substrate is subjected to sandblasting treatment, and then cleaned and dried to obtain a pretreated substrate; water is used for cleaning; the drying temperature is 80° C.; the drying time is 1 h; the substrate is a titanium tube; the sandblasting material is alumina sand with a particle size of 20 / 40 mesh, and the sandblasting pressure is 0.3 MPa;
[0064] (2) adding polyvinyl alcohol to 80° C. hot water, stirring while adding, aging for 12 hours after dissolution, to obtain a colloidal solution; wherein the mass ratio of polyvinyl alcohol to hot water is 1:10;
[0065] (3) adding titanium powder, titanium-nickel alloy powder and nickel-titanium fiber wire to the colloidal solution obtained in step (2) in sequence, stirring while adding, to obtain a powder slurry; wherein the average particle size of the titanium powder is 50 μm; the nickel content of the titanium-nickel alloy powder is 36 wt.%, and the average particle size is 20 μm; the titanium content of the nickel-titanium fiber wire is 38 wt.%, the wire diameter is 10 μm, and the length is 100 μm; the mass ratio of the titanium powder, the titanium-nickel alloy powder and the nickel-titanium fiber wire is 5:1:0.2; the mass ratio of the sum of the mass of the titanium powder, the titanium-nickel alloy powder and the nickel-titanium fiber wire to the colloidal solution is 1.5:1;
[0066] (4) coating the powder slurry obtained in step (3) on the surface of the pretreated substrate obtained in step (1); after coating, applying a uniform magnetic field around the titanium tube to dry the surface film layer under the action of the magnetic field to obtain a surface film tube; wherein the magnetic induction intensity of the magnetic field is 0.3 T, and the thickness of the surface film layer is 200 μm;
[0067] (5) heat treating the surface film tube obtained in step (4) and cooling it to obtain a surface porous tube. The heat treatment is carried out in a vacuum atmosphere, and the heat treatment includes degreasing and sintering; the degreasing temperature is 250°C and the holding time is 60 minutes; the sintering temperature is 980°C and the holding time is 20 minutes, and the cooling rate is 8°C / min.
[0068] The bonding strength between the porous layer and the base tube of this embodiment is 22Mpa, and the titanium-based surface porous tube has a heat flux range of 10-60kW / m 2 The boiling heat transfer coefficient is about 2.3 to 3.5 times that of a light tube.
[0069] Example 2
[0070] The method for preparing the titanium-based surface porous tube of this embodiment comprises the following steps:
[0071] (1) The surface of the substrate is subjected to sandblasting treatment, and then cleaned and dried to obtain a pretreated substrate; the cleaning is carried out using alcohol; the drying temperature is 70° C.; the drying time is 0.5 h; the substrate is a titanium tube; the sandblasting material is alumina sand with a particle size of 20 / 40 mesh, and the sandblasting pressure is 0.3 MPa;
[0072] (2) adding polyethylene glycol to 50° C. hot water, stirring while adding, aging for 24 hours after dissolution, to obtain a colloidal solution; wherein the mass ratio of polyethylene glycol to hot water is 1:15;
[0073] (3) adding titanium powder, titanium-nickel alloy powder and nickel-titanium fiber wire to the colloidal solution obtained in step (2) in sequence, stirring while adding, to obtain a powder slurry; wherein the average particle size of the titanium powder is 100 μm; the nickel content of the titanium-nickel alloy powder is 33 wt.%, and the average particle size is 30 μm; the titanium content of the nickel-titanium fiber wire is 40 wt.%, the wire diameter is 20 μm, and the length is 200 μm; the mass ratio of the titanium powder, the titanium-nickel alloy powder and the nickel-titanium fiber wire is 4:1:0.3; the mass ratio of the sum of the mass of the titanium powder, the titanium-nickel alloy powder and the nickel-titanium fiber wire to the colloidal solution is 2.5:1;
[0074] (4) coating the powder slurry obtained in step (3) on the surface of the pretreated substrate obtained in step (1); after coating, applying a uniform magnetic field around the titanium tube to dry the surface film layer under the action of the magnetic field to obtain a surface film tube; wherein the magnetic induction intensity of the magnetic field is 0.5 T, and the thickness of the surface film layer is 300 μm;
[0075] (5) heat treating the surface film tube obtained in step (4) and cooling it to obtain a surface porous tube. The heat treatment is carried out in a vacuum atmosphere, and the heat treatment includes degreasing and sintering; the degreasing temperature is 320°C and the holding time is 90 minutes; the sintering temperature is 1000°C, the holding time is 30 minutes, and the cooling rate is 7.5°C / min.
[0076] The bonding strength between the porous layer and the base tube of this embodiment is 23Mpa, and the titanium-based surface porous tube has a heat flux range of 10-60kW / m 2 The boiling heat transfer coefficient is about 2.8 to 4.0 times that of a light tube.
[0077] Example 3
[0078] The method for preparing the titanium-based surface porous tube of this embodiment comprises the following steps:
[0079] (1) The surface of the substrate is subjected to sandblasting treatment, and then cleaned and dried to obtain a pretreated substrate; water is used for cleaning; the drying temperature is 60° C.; the drying time is 2 h; the substrate is a titanium tube; the sandblasting material is alumina sand with a particle size of 20 / 40 mesh, and the sandblasting pressure is 0.3 MPa;
[0080] (2) adding polyvinyl butyral to ethanol, stirring while adding, aging for 24 hours after dissolution, to obtain a colloidal solution; wherein the mass ratio of polyvinyl butyral to ethanol is 1:30;
[0081] (3) adding titanium powder, titanium-nickel alloy powder and nickel-titanium fiber wire to the colloidal solution obtained in step (2) in sequence, stirring while adding, to obtain a powder slurry; wherein the average particle size of the titanium powder is 150 μm; the nickel content of the titanium-nickel alloy powder is 28 wt.%, and the average particle size is 50 μm; the titanium content of the nickel-titanium fiber wire is 22 wt.%, the wire diameter is 30 μm, and the length is 300 μm; the mass ratio of the titanium powder, the titanium-nickel alloy powder and the nickel-titanium fiber wire is 3:1:0.5; the mass ratio of the sum of the mass of the titanium powder, the titanium-nickel alloy powder and the nickel-titanium fiber wire to the colloidal solution is 3.5:1;
[0082] (4) coating the powder slurry obtained in step (3) on the surface of the pretreated substrate obtained in step (1); after coating, applying a uniform magnetic field around the titanium tube to dry the surface film layer under the action of the magnetic field to obtain a surface film tube; wherein the magnetic induction intensity of the magnetic field is 0.7 T, and the thickness of the surface film layer is 400 μm;
[0083] (5) heat treating the surface film tube obtained in step (4) and cooling it to obtain a surface porous tube. The heat treatment is carried out in a vacuum atmosphere, and the heat treatment includes degreasing and sintering; the degreasing temperature is 450°C and the holding time is 30 minutes; the sintering temperature is 940°C and the holding time is 60 minutes; and the cooling rate is 7.5°C / min.
[0084] The bonding strength between the porous layer and the base tube of this embodiment is 25Mpa, and the titanium-based surface porous tube has a heat flux range of 10-60kW / m 2 The boiling heat transfer coefficient is about 3.1 to 4.5 times that of a light tube.
[0085] Comparative Example
[0086] Comparative Example 1
[0087] The preparation method of the titanium-based surface porous tube of this comparative example is different from that of Example 1 in that it comprises the following steps:
[0088] (1) The surface of the substrate is subjected to sandblasting treatment, and then cleaned and dried to obtain a pretreated substrate; water is used for cleaning; the drying temperature is 80° C.; the drying time is 1 h; the substrate is a titanium tube; the sandblasting material is alumina sand with a particle size of 20 / 40 mesh, and the sandblasting pressure is 0.3 MPa;
[0089] (2) adding polyvinyl alcohol to 80° C. hot water, stirring while adding, aging for 12 hours after dissolution, to obtain a colloidal solution; wherein the mass ratio of polyvinyl alcohol to hot water is 1:10;
[0090] (3) adding titanium powder to the colloidal solution obtained in step (2), stirring while adding, to obtain a powder slurry; wherein the average particle size of the titanium powder is 50 μm;
[0091] (4) coating the powder slurry obtained in step (3) on the surface of the pretreated substrate obtained in step (1); after coating, drying the titanium tube to obtain a surface film tube; wherein the thickness of the surface film layer is 200 μm;
[0092] (5) heat treating the surface film tube obtained in step (4) and cooling it to obtain a surface porous tube. The heat treatment is carried out in a vacuum atmosphere, and the heat treatment includes degreasing and sintering; the degreasing temperature is 250°C and the holding time is 60 minutes; the sintering temperature is 1150°C and the holding time is 60 minutes; and the cooling rate is 8°C / min.
[0093] The bonding strength between the porous layer and the base tube of this comparative example is 15Mpa, and the titanium-based surface porous tube has a heat flux range of 10-60kW / m 2 The boiling heat transfer coefficient is about 1.5 to 2.2 times that of a light tube.
[0094] Comparative Example 2
[0095] The preparation method of the titanium-based surface porous tube of this comparative example is different from that of Example 1 in that it comprises the following steps:
[0096] (1) The surface of the substrate is subjected to sandblasting treatment, and then cleaned and dried to obtain a pretreated substrate; water is used for cleaning; the drying temperature is 80° C.; the drying time is 1 h; the substrate is a titanium tube; the sandblasting material is alumina sand with a particle size of 20 / 40 mesh, and the sandblasting pressure is 0.3 MPa;
[0097] (2) adding polyvinyl alcohol to 80° C. hot water, stirring while adding, aging for 12 hours after dissolution, to obtain a colloidal solution; wherein the mass ratio of polyvinyl alcohol to hot water is 1:10;
[0098] (3) adding titanium powder and titanium-nickel alloy powder to the colloidal solution obtained in step (2) in sequence, stirring while adding, to obtain a powder slurry; wherein the average particle size of the titanium powder is 50 μm; the nickel content of the titanium-nickel alloy powder is 36 wt.%, and the average particle size is 20 μm; the mass ratio of the titanium powder to the titanium-nickel alloy powder is 5:1; and the mass ratio of the sum of the mass of the titanium powder and the titanium-nickel alloy powder to the colloidal solution is 1.5:1;
[0099] (4) coating the powder slurry obtained in step (3) on the surface of the pretreated substrate obtained in step (1); after coating, drying the titanium tube to obtain a surface film tube; wherein the thickness of the surface film layer is 200 μm;
[0100] (5) heat-treating the surface film tube obtained in step (4) and cooling it to obtain a surface porous tube. The heat treatment is carried out in a vacuum atmosphere, and the heat treatment includes degreasing and sintering; the degreasing temperature is 250°C and the holding time is 60 minutes; the sintering temperature is 980°C and the holding time is 20 minutes; and the cooling rate is 8°C / min.
[0101] The bonding strength between the porous layer and the base tube of this comparative example is 20Mpa, and the titanium-based surface porous tube has a heat flux range of 10-60kW / m 2 The boiling heat transfer coefficient is about 1.4 to 2.1 times that of a bare tube.
[0102] Comparative Example 3
[0103] The preparation method of the titanium-based surface porous tube of this comparative example is different from that of Example 1 in that it comprises the following steps:
[0104] (1) The surface of the substrate is subjected to sandblasting treatment, and then cleaned and dried to obtain a pretreated substrate; water is used for cleaning; the drying temperature is 80° C.; the drying time is 1 h; the substrate is a titanium tube; the sandblasting material is alumina sand with a particle size of 20 / 40 mesh, and the sandblasting pressure is 0.3 MPa;
[0105] (2) adding polyvinyl alcohol to 80° C. hot water, stirring while adding, aging for 12 hours after dissolution, to obtain a colloidal solution; wherein the mass ratio of polyvinyl alcohol to hot water is 1:10;
[0106] (3) adding titanium powder, titanium-nickel alloy powder and titanium fiber to the colloidal solution obtained in step (2) in sequence, stirring while adding, to obtain a powder slurry; wherein the average particle size of the titanium powder is 50 μm; the nickel content of the titanium-nickel alloy powder is 36 wt.%, and the average particle size is 20 μm; the wire diameter of the titanium fiber is 10 μm, and the length is 100 μm; the mass ratio of the titanium powder, the titanium-nickel alloy powder and the titanium fiber is 5:1:0.2; the mass ratio of the sum of the mass of the titanium powder, the titanium-nickel alloy powder and the titanium fiber to the colloidal solution is 1.5:1;
[0107] (4) coating the powder slurry obtained in step (3) on the surface of the pretreated substrate obtained in step (1); after coating, applying a uniform magnetic field around the titanium tube to dry the surface film layer under the action of the magnetic field to obtain a surface film tube; wherein the magnetic induction intensity of the magnetic field is 0.3 T, and the thickness of the surface film layer is 200 μm;
[0108] (5) heat-treating the surface film tube obtained in step (4) and cooling it to obtain a surface porous tube. The heat treatment is carried out in a vacuum atmosphere, and the heat treatment includes degreasing and sintering; the degreasing temperature is 250°C and the holding time is 60 minutes; the sintering temperature is 980°C and the holding time is 20 minutes; and the cooling rate is 8°C / min.
[0109] The bonding strength between the porous layer and the base tube of this embodiment is 22Mpa, and the titanium-based surface porous tube has a heat flux range of 10-60kW / m 2 The boiling heat transfer coefficient is about 1.8 to 2.6 times that of a light tube.
[0110] Performance Testing
[0111] Porosity detection method of porous layer: The titanium-based surface porous tube prepared in Examples 1-3 was used to detect the porosity of the porous layer according to the detection method in GB / T 15749-2008 "Quantitative Metallographic Determination Method". The porosity detection results are shown in Table 1.
[0112] Porous layer equivalent pore size detection method: Use the infiltration method to detect, immerse one end of the tube vertically in diesel, measure the capillary climbing height of diesel along the porous layer, and calculate the equivalent pore size of the porous layer according to the following formula:
[0113]
[0114] Where d is the equivalent pore size of the porous layer, m; σ is the surface tension coefficient of the wetting liquid, N / m; ρ is the density of the wetting liquid, kg / m 3 ; g is the acceleration due to gravity (9.80 m / s 2 ), h is the climbing height of the wetting liquid, m, and θ is the contact angle between the wetting liquid and the solid surface.
[0115] Method for testing the bonding strength between the porous layer and the base tube: The titanium-based surface porous tube prepared in Example 1-3 was tested for interface bonding strength using a universal testing machine according to the testing method in YS / T485-2005 "Method for Determining Shear Strength of Sintered Bimetallic Materials". The test results are shown in Table 1.
[0116] Table 1 Performance test results of titanium-based porous tubes in Examples 1-3 and Comparative Examples 1-3
[0117] Serial number Porosity of porous layer % Equivalent pore size μm Bonding strength MPa Sintering temperature℃ Example 1 50 60 22 980 Example 2 55 70 23 1000 Example 3 58 80 25 940 Comparative Example 1 40 45 15 1150 Comparative Example 2 38 42 20 980 Comparative Example 3 45 53 22 980
[0118] In combination with Examples 1-3 and the data in Table 1, it can be seen that the porosity of the titanium-based surface porous tubes obtained in Examples 1-3 is greater than 50%, and the maximum is as high as 58%; the equivalent pore size distribution is 60-80 μm, the bonding strength exceeds 21 MPa, and the boiling heat transfer coefficient of the titanium-based surface porous tube is about 2.3-4.5 times that of the light tube, and the maximum is up to 4.5 times, the heat transfer coefficient is greatly improved, and the titanium-based surface porous tubes of Examples 1-3 are sintered during the preparation process at a relatively low temperature, as low as 940°C. The titanium-based surface porous tubes obtained by the preparation method of the present invention have high porosity, good bonding strength, a more significant improvement in boiling heat transfer coefficient, and better heat transfer performance.
[0119] In combination with Example 1 and Comparative Example 1, and in combination with the data in Table 1, it can be seen that the porosity, equivalent pore size, bonding strength, and boiling heat transfer coefficient of the porous layer of the titanium-based surface porous tube of Example 1 are all greater than the porosity, equivalent pore size, bonding strength, and boiling heat transfer coefficient of the porous layer of the titanium-based surface porous tube prepared in Comparative Example 1, and the sintering temperature of the titanium-based surface porous tube of Example 1 is lower than the sintering temperature of the titanium-based surface porous tube of Comparative Example 1. The difference between Example 1 and Comparative Example 1 is that the metal material in Comparative Example 1 is only titanium powder. It can be found that by combining titanium powder, titanium-nickel alloy powder and nickel-titanium fiber filaments, the titanium-nickel alloy powder generates a liquid phase during the sintering process, so that the titanium powder forms a strong metallurgical bond at a lower sintering temperature, and the titanium-based surface porous tube thus prepared has better performance in all aspects.
[0120] In combination with Example 1 and Comparative Example 2, and in combination with the data in Table 1, it can be seen that the performance of the titanium-based surface porous tube in Example 1 is better than that of the titanium-based surface porous tube in Comparative Example 2. The difference between Example 1 and Comparative Example 2 is that: No nickel-titanium fiber wire is added in Comparative Example 2, and the boiling heat transfer coefficient of the titanium-based surface porous tube thus obtained is not good, the porosity of the porous layer is relatively poor, and the equivalent pore size and bonding strength are also relatively poor. In Example 1, three components of titanium powder, titanium-nickel alloy powder and nickel-titanium fiber wire are added at the same time, and the three components cooperate with each other, so that the titanium-based surface porous tube obtained has excellent performance in all directions.
[0121] Combining Example 1 and Comparative Example 3, and combining the data in Table 1, it can be seen that the boiling heat transfer coefficient, porous layer porosity, and equivalent pore size of the titanium-based surface porous tube of Example 1 are better than those of the titanium-based surface porous tube of Comparative Example 3. The difference between Example 1 and Comparative Example 3 is that Comparative Example 3 uses titanium fiber to replace the nickel-titanium fiber wire in Example 1. Since titanium fiber is not magnetic, it will not be radially distributed along the radial direction of the titanium tube under the action of the magnetic field. Therefore, the overall performance of the titanium-based surface porous tube obtained in Comparative Example 3 is poor.
[0122] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing a titanium-based surface porous tube, characterized in that: The steps include: (1) pretreating a substrate to obtain a pretreated substrate; (2) mixing the binder and the solvent, aging, and obtaining a colloidal solution; (3) adding titanium powder, titanium-nickel alloy powder and nickel-titanium fiber wire to the colloidal solution obtained in step (2) in sequence, stirring to obtain a powder slurry; (4) coating the powder slurry obtained in step (3) on the surface of the pretreated substrate obtained in step (1), and drying under magnetic field conditions to obtain a surface film tube; (5) heat-treating the surface film tube obtained in step (4), cooling it, and obtaining a surface porous tube.
2. The method for preparing a titanium-based surface porous tube according to claim 1, characterized in that: Also includes one or more of the following features: 11) The pretreatment in step (1) is surface treatment of the substrate, followed by cleaning and drying. Preferably, the surface treatment is selected from one or more of pickling, laser rust removal, mechanical grinding, sandblasting, and passivation; 12) The substrate in step (1) is selected from titanium or titanium-based alloy.
3. The method for preparing a titanium-based surface porous tube according to claim 1, characterized in that: The step (2) further includes one or more of the following features: 21) In step (2), the binder is selected from one or more of polyvinyl alcohol, polyethylene glycol, polyvinyl butyral, polyvinyl pyrrolidone, and methyl cellulose; 22) The solvent in step (2) is selected from one or more of water, methanol, ethanol, ethylene glycol, benzene, and toluene. Preferably, the solvent in step (2) is selected from water or ethanol; 23) In step (2), the mass ratio of the binder to the solvent is 1:10 to 40; 24) The aging time in step (2) is 12 to 24 hours; 25) The mixing temperature in step (2) is 40 to 90°C.
4. The method for preparing a titanium-based surface porous tube according to claim 1, characterized in that: The step (3) further includes one or more of the following features: 31) In step (3), the mass ratio of titanium powder, titanium-nickel alloy powder and nickel-titanium fiber is 3-5:1:0.2-0.5; 32) The average particle size of the titanium powder in step (3) is 50 to 150 μm; 33) The average particle size of the titanium-nickel alloy powder in step (3) is 20 to 50 μm; 34) In step (3), the diameter of the nickel-titanium fiber is 10 to 30 μm, and the length is 100 to 300 μm; 35) In step (3), the mass ratio of the titanium powder, titanium-nickel alloy powder and nickel-titanium fiber filament to the colloidal solution is 1.5 to 3.5:
1.
5. The method for preparing a titanium-based surface porous tube according to claim 4, characterized in that: 331) The nickel content of the titanium-nickel alloy powder is 28wt.% to 38wt.%; 341) The titanium content of the nickel-titanium fiber wire is 22wt.% to 45wt.%.
6. The method for preparing a titanium-based surface porous tube according to claim 1, characterized in that: The step (4) further includes one or more of the following features: 41) The thickness of the surface film layer of the surface film tube in step (4) is 200 to 400 μm; 42) The magnetic induction intensity of the magnetic field drying in step (4) is 0.3 to 0.7 T; 43) The drying temperature is 50-70°C and the drying time is 1-2h.
7. The method for preparing a titanium-based surface porous tube according to claim 1, characterized in that: The step (5) further includes one or more of the following features: 51) The heat treatment in step (5) includes degreasing and sintering; 52) The heat treatment in step (5) is carried out under vacuum or inert gas atmosphere; 53) The cooling in step (5) includes furnace cooling and / or water cooling.
8. The method for preparing a titanium-based surface porous tube according to claim 7, characterized in that: The degreasing temperature is 250-450° C., and the heat preservation time is 30-90 minutes; the sintering temperature is 900-1100° C., and the heat preservation time is 20-60 minutes.
9. A titanium-based surface porous tube, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.
10. The titanium-based surface porous tube according to claim 9, characterized in that: The titanium-based surface porous tube comprises a substrate and a porous layer formed on the surface of the substrate; preferably, the thickness of the porous layer is 200 to 400 μm.
Citation Information
Patent Citations
High-flux high-titanium heat exchange tube and preparation method thereof
CN113834365A
Titanium-based high-flux heat exchange tube and preparation method and application thereof
CN116180190A